UMA RAZÃO QUE SE EXPRESSA: DEVANEANDO COM ROUSSEAU - Campos, Douglas; de Sant’Anna Alves Primo, Marcelo (Prometheus - Journal of Philosophy., 2020)
Jean-Jacques Rousseau (1712-1778), when he was 65 years old, in 1777, wrote his Daydreams of the lonely walker. In the work, the author chooses reverie as a philosophical methodology. The purpose of this text is to appropriate the idea of Rousseaunian reverie, and to instrumentalize it in the idea of experience. This instrumentalization will be carried out through the mechanism of contemplation. Since contemplation is the activity of lingering, intermingling, conservation and astonishment for the “being-so” of things, one seeks, by appealing to its mechanism, to curb the process of aggression to the environment in its dynamics of hyperproductivity .